The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.26650/eurjbiol.2019.0001
|View full text |Cite
|
Sign up to set email alerts
|

Metal Bioaccumulation of Mytilaster lineatus (Gmelin, 1791) Collected From Sinop Coast in the Southern Black Sea

Abstract: Objective: Metal bioaccumulation of the bivalve Mytilaster lineatus, based on different seasons and stations was investigated in Sinop Peninsula of the Black Sea. Soft tissues of mussels from Gazibey Rock and Içliman were taken during the spring and the summer of the year 2016 and were analyzed for Hg, Cd, Pb, Cu and Zn. Methods: The soft tissues of the mussels digested with Suprapur® HNO3 (nitric acid) using a Milestone Systems, Start D 260 microwave digestion system. The accuracy and precision of the method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…However, recent literature has shown that the amount of freshwater discharge of particulate Hg in this locality, and its bioaccumulation in marine biota, is negligible compared to other trace elements (e.g. < 50 ng.g -1 ww in fish liver, < DL in invertebrates) (Bat et al, 2019(Bat et al, , 2018. Therefore, our Black Sea sampling site can be considered as a relatively unpolluted area with regards to Hg (Table 1), excluding the hypothesis of a particular point source of anthropogenic origin.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 86%
“…However, recent literature has shown that the amount of freshwater discharge of particulate Hg in this locality, and its bioaccumulation in marine biota, is negligible compared to other trace elements (e.g. < 50 ng.g -1 ww in fish liver, < DL in invertebrates) (Bat et al, 2019(Bat et al, , 2018. Therefore, our Black Sea sampling site can be considered as a relatively unpolluted area with regards to Hg (Table 1), excluding the hypothesis of a particular point source of anthropogenic origin.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 86%